Evaluation Analysis Of Internal Control Of The Cash Expenditure Accounting System In Bumdes Harapan Makmur, Tebing Tinggi Village - M. Irwan; Diskhamarzaweny Diskhamarzaweny; Yul Emri Yulis (International Journal of Business and Quality Research, 2024)
Research Object in a Village-Owned Enterprise with the name Harapan Makmur which is domiciled in Tebing Tinggi Village. The aim of the research is in the context of internal control of the Harapan Makmur Village-Owned Enterprise. As well as to explain technically related cash expenditures carried out by the Harapan Makmur Village-Owned Enterprise. Then the essence of this main research problem is: how to implement the internal control system of the Harapan Makmur Village-Owned Enterprise, whether it is in accordance or not in accordance with the internal control system contained in the COSO theory. Meanwhile, the type of research is a case study in implementing COSO in Harapan Makmur Village-Owned Enterprises, Tebing Tinggi Village, Kec. Benai, Kab. Kuansing, Prov. Riau. So data collection techniques can be used through methods, observation, interviews and documentation. How to analyze data using conformity and compliance tests and theory. Thus, the research results show that almost all indicators from the COSO theory show that they are appropriate except for two sub-sections of research indicators that are not appropriate, namely environmental performance monitoring and control.